Albert Bandura's Social Learning Theory and Its Relevance in Modern Learning - Farhan Aprisal; Milda Apriliana (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Learning in the modern era demands an adaptive, collaborative, and technology-based approach. One theory that is highly relevant in this context is Albert Bandura's Social Learning Theory, which emphasizes that humans learn not only through direct experience but also through observation, imitation, and modeling. This study aims to examine the relevance and implications of Bandura's theory in modern learning practices. The research method used is a desk study, reviewing various literature and current research related to social learning theory, self-efficacy, and their application in digital technology-based learning. The results of the discussion highlight three main points. First, observational learning and modeling play a crucial role in modern education, where teachers, peers, and digital media can serve as effective learning models. Second, self-efficacy has been shown to have a significant influence on student learning motivation, resilience in the face of challenges, and academic achievement. Third, the development of digital technology expands the scope of Bandura's theory by presenting new opportunities and challenges in online, collaborative, and media-based learning. In conclusion, Albert Bandura's social learning theory remains relevant as a strategic foundation for designing modern learning that can build students' motivation, achievement, and adaptive skills in the 21st century.